Bakteri Asam Laktat Kandidat Probiotik dari Susu Kuda Bima: Lactic Acid Bacteria from Bima Horse’s Milk as a Probiotic Candidates - Dewi Asnita; Anja Meryandini (Jurnal Sumberdaya Hayati, 2023)
Awareness of the role of healthy food has led to increased public interest in healthy food that has additional functions than as energy fulfillment. One form of the healthy foods is food that contains probiotics, so this study aims to select lactic acid bacteria from milk as probiotic candidates. Lactic acid bacteria isolates from goat, horse and buffalo milk in Indonesia were studied to find the best probiotic candidates out of 100 isolates. Parameters which are measured in this study included resistance to gastric acid, bile salts, aggregation, autoaggregation abilities, and sensitivity to antibiotics. One isolate from bima horse’s milk has the potency as a probiotic candidate. The bacterial isolate from Bima horse’s milk has the character of being resistant to acids, and bile salts, sensitive to the two antibiotics tested and can aggregate with Salmonella Thypimurium. From molecular identification, the selected Bima horse’s milk isolate has similarities with Lacticaseibacillus rhamnosus strain MG5511.